Bistable liquid crystal display - Than Win Soe. (2008)
In this research work, a 16 x16 dot matrix (0, 2pi) bistable twisted nematic (BTN) liquid crystal display was successfully fabricated and their bi stability were observed. And some (-pi/2, 3pi/2) BTNs were also tested. They all were in the same type of 2pi twisted BTN. The display panel was made by the use of MLC 15700-000 doped with chiral additive ZLI-811 (Merck). This display was operated with special switching waveforms. It can stay for several minutes at the two bistable states without holding voltage and has much higher contrast ratio than TN or STN displays with large viewing angle due to homogeneous switching in both states.